Preferential origin and layer destination of GAD65-GFP cortical interneurons. - López-Bendito, G; Sturgess, K; Erdélyi, F; Szabó, G; Molnár, Z; Paulsen, O (2004)
To identify the origin and track the migratory pathway of specific subpopulations of GABAergic interneurons, we studied tangential migration in a recently developed GAD65-GFP transgenic mouse strain. First, we used immunohistochemical methods to characterize the expression of specific neurochemical markers in the GAD65-GFP neurons. Then, organotypic cultures were used in combination with birth-dating studies to determine the time of generation, place of origin and migratory route of these cells. From E14 to E15, the highest density of GAD65-GFP cells was seen in the lower intermediate zone; however, at later stages more GAD65-GFP cells were observed in the subventricular zone. Migratory GAD65-GFP cells express GAD65, but not calretinin or reelin. Surprisingly, only 4% were calbindin immunopositive. At P21, GAD65-GFP cells were found predominantly in layers II-III and expressed calretinin and neuropeptide Y. Remarkably, almost all cholecystokinin-positive but very few parvalbumin-positive neurons expressed GFP. In vitro studies demonstrated that the caudal ganglionic eminence gives rise to a large proportion of GAD65-GFP interneurons and in vivo birth-dating experiments showed that GAD65-GFP interneurons in supragranular layers are born at late embryonic development. Taken together these results support the idea that the destination layer of GABAergic interneurons is closely linked to their place of origin and time of generation.